Geochemistry and Petrogenesis of Mata Lower Jurassic basaltic rocks, Southeast Kerman, Implication to Southern Sanandaj-Sirjan zone evolution - Zahra Badrzadeh (پترولوژی, 2019)
Lower Jurassic volcanic-sedimentary sequence in the southern end of the Sanandaj-Sirjan zone, north of Mata village (southwest Jiroft), composed of tuffaceous limestone, calcareous tuff, limestone, including felsic volcaniclastic and basaltic volcanic rocks with northwest-southeast trend; which here geochemical characteristics and petrogenesis of the basaltic rocks of this sequence have been studied. Basalts texture is dominantly microporphyritic with clinopyroxene and plagioclase as the main minerals set in an intergranular to intersertal of plagioclase, clinopyroxene, apatite, opaque minerals and chlorite originally glassy matrix. On the basis of petrographic and geochemical data, basaltic rocks have tholeiitic affinity. These basalts are Light REE-depleted tholeiites similar to REE pattern of the N-MORB, However they are characterized by the enrichment of LILE over HFSE and negative Nb–Ta anomalies which are subduction zone trace element signatures. Based on trace element ratios, Mata basaltic rocks were derived from partial melting of a depleted lithospheric mantle source which enriched by subduction zone components. Meanwhile they fractionated on upwelling. Based on field and geochemical data, Mata basalts are interpreted to have formed in an initial back-arc basin behind the Sanandaj-Sirjan magmatic arc at Lower Jurassic time.